Association of aldehyde dehydrogenase 2gene polymorphism with multiple oesophageal dysplasia in head and neck cancer patients. (1st August 2000) - Muto, M; Hitomi, Y; Ohtsu, A; Ebihara, S; Yoshida, S; Esumi, H
Abstract : BACKGROUND: Multiple occurrences of oesophageal dysplasia are frequently observed in head and neck cancer patients, and closely associated with alcohol consumption. Acetaldehyde, the first metabolite of ethanol, is thought to play an important role in the carcinogenesis of the upper aerodigestive tract. AIM: To investigate if genetic polymorphism in alcohol metabolising enzymes (ADH3, alcohol dehydrogenase 3; ALDH2, aldehyde dehydrogenase 2) is associated with oesophageal multiple dysplasia in head and neck cancer patients. METHODS: Thirty one consecutive patients with head and neck cancer were included in the study. Multiple oesophageal dysplasia was detected endoscopically as multiple Lugol voiding lesions (multiple LVL) using the Lugol dye staining method. The ADH3 and ALDH2 genotypes were determined by polymerase chain reaction-restriction fragment length polymorphism. RESULTS: Among the 31 patients with head and neck cancer, 17 had multiple LVL. Multiple LVL were closely associated with a second primary oesophageal carcinoma in head and neck cancer patients (odds ratio 60.7, 95% CI 5.6–659). Furthermore, the mutant ALDH2 allele was significantly more prevalent in patients with multiple LVL (65% v 29%; p<0.05) whereas no difference was observed in ADH3 polymorphism. CONCLUSIONS: The mutant ALDH2 allele appears to be a risk indicator for multiple LVL in head and neck cancer patients. Accumulation of acetaldehyde due to low ALDH2 activity may play a critical role in cancerous changes throughout the mucosa in the upper aerodigestive tract.